Examining the Locus of Control, Auditor Experience, Self-Efficacy and Task Complexity for Audit Judgment - Sabilillah, Rhalia; Hardi, Hardi; Safitri, Devi (Studi Akuntansi dan Keuangan Indonesia, 2024)
This research goals to specify The Influence of Locus of Control, Auditor Experience, Self-efficacy and Task Complexity on Audit judgment (Empirical study at KAP in Pekanbaru and Padang). This research method use quantitative research method. The occupant in this research are auditors in the Pekanbaru and Padang areas. The sample in this study was 39. Data analysis was brought out use classic contention tests and hypothesis examine using the lots of regression method. The difference between this study and the reference journal (Yowanda et al. 2019) is the location of the study, the variables used and the year of the study. Based on the research yields, it shows that The Auditor's Experience, Self-efficacy and Task Complexity have an influence on Audit judgment in the Pekanbaru and Padang areas, while the Locus of Control variable hasn’t clout on Audit judgment in the Pekanbaru and Padang areas.